Mediterranean fever gene variants modify clinical phenotypes of idiopathic multi‐centric Castleman disease - Endo, Yushiro; Koga, Tomohiro; Ubara, Yoshihumi; Sumiyoshi, Remi; Furukawa, Kaori; Kawakami, Atsushi (Clinical and experimental immunology, 2021)
Four cases of idiopathic multi‐centric Castleman disease (iMCD) reportedly have variants in hereditary autoinflammatory disease‐related genes; however, the frequency and role of these variants in iMCD is still unknown. We therefore investigated such gene variants among patients with iMCD and aimed to reveal the relationship between iMCD and autoinflammatory disease‐related genes. We reviewed 14 Japanese iMCD patients who were recruited between January 2015 and September 2019. All patients met both the Japanese tentative diagnostic criteria for Castleman disease and the international consensus diagnostic criteria for iMCD. We performed genetic analyses for 31 autoinflammatory disease‐related genes by targeted next‐generation sequencing. The MEFV gene variants were observed in 10 of 14 patients with iMCD. Although iMCD had a high percentage of exons 2 or 3 variants of MEFV, comparison of data from healthy Japanese subjects indicated that there was no significant difference in the percentage between healthy Japanese subjects and patients with iMCD. Variants of uncertain significance (VUS) in the TNFRSF1A and CECR1 genes were observed in two of the patients, respectively. We divided patients into two groups—those with MEFV variants (excluding E148Q variants) and those without MEFV variants—and compared the clinical characteristics between these two groups. Patients with MEFV variants, excluding E148Q variants, exhibited a significantly higher likelihood of fever and significantly lower levels of hemoglobin than those lacking MEFV variants. Our results indicated that patients with iMCD tended to have a high frequency of MEFV gene variants and the presence of such variants can affect iMCD clinical phenotypes. Patients with idiopathic multicentric Castleman's disease who have variants of the MEFV gene may have severe degrees of fever and anemia due to increased inflammatory cytokines associated with autoinflammatory diseases.